Floristic Diversity of the Katepurna Wildlife Sanctuary of Akola Wildlife Division, Maharashtra - Hande, Nitesh S.; Nimkar, A. U.; Taide, Y. B.; Mankar, R. D. (Indian Forester, 2014)
The present work was carried out in Katepurna wildlife sanctuary of Maharashtra. During survey 94 plant species belonging to 76 genera and 36 families have been collected and documented. Out of these, 79 species within 63 genera of 33 families belong to dicots, 15 species in 13 genera of 3 families belong to monocot. Data reveals that dicots dominate over monocots in the vegetation of the area.